(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. For childhood characterized by the development of postoperative inflammatory complications after surgery for complications of uveal cataracts. Currently, in order to prevent postoperative inflammatory glucocorticosteroids are used since they are pathogenic in treating uveitis. Aim. To develop a method of preventing postoperative inflammation expressed in uveal surgery complicated cataract in children. Material and Methods. 22 children were operated on (26 eyes) with complicated uveal cataract in age from 4 to 17 years. Before the operation on the operating table all patients underwent prolonged corticosteroid injection subtenon kenalogom. Cataract surgery was performed by various methods lensectomy. Results. It is revealed that the developed method for the prevention of postoperative inflammation in cataract surgery complicated uveal children to avoid the development of severe postoperative osloneny. Conclusion. The developed method for the prevention of postoperative inflammation expressed in response to eye surgery to remove cataracts complicated uveal thatprevents the development of severe postoperative complications.